The US's Economic Promises Are Over: An Interview with Miguel Luciano. (3rd April 2018) - Lerer, Marisa; McGarrigle, Conor
Abstract : Hurricane Maria struck Puerto Rico in September 2017. The island was left without electricity and clean water for months. However, the natural disaster was not the only cause of this lasting devastation. The financial fall-out from predatory loans, which led to Puerto Rico's inability to invest funds in its own infrastructure, caused an enduring humanitarian disaster. Artist Miguel Luciano (b. 1972) in this interview discusses his work in relation to the 2017 Puerto Rican debt crisis and the legacy of the over 100-year span of Puerto Rico's colonial status as a US territory, which gives the US disproportionate control over the island's economy. Luciano's aesthetic economic investigations also examine the impact of the financial crisis and immigration on the Puerto Rican diaspora living in the US mainland.